Adaptive Design Applied to Identification of the Minimum Effective Dose in Schizophrenia: Simulations of Scientific and Commercial Value. (January 2014) - Parke, Tom; Dragalin, Vladimir; Turkoz, Ibrahim; Marchenko, Olga; Haynes, Virginia
The International Society for CNS Clinical Trials and Methodology (ISCTM) Adaptive Design Working Group (IADWG) designed a case study simulation exercise to compare the value of traditional versus adaptive design approaches to phase II clinical trial design in schizophrenia in statistical and economic terms. Operational characteristics of both designs were compared across 7 likely dose-response curves. Based on IADWG members' recent research experience in schizophrenia, estimates of expected net present value (eNPV) for the molecule were compared for the traditional and adaptive designs. Across dose-response curve scenarios with a minimum effective dose (MED), the adaptive design was more likely to show proof of concept and correctly identify the MED than was the traditional design. Even with a conservative weighting of possible dose-response curves, using an adaptive design in phase II resulted in higher eNPV. This simulation supports the statistical and economic value for decision makers exploring the use of adaptive approaches to phase II research in schizophrenia.